Youth unemployment, deviance and state : a case study of educated youths in Kano, Nigeria - Surajo, Aminu Zubairu (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
Unemployment among educated youths is a serious phenomenon in Nigeria. It constitutes a problem not only for the youths themselves but to the overall social, political and economic structures of the country. Therefore, it is important to conduct an empirical investigation on this issue in order to generate data which are needed in resolving youth unemployment. The present study aimed at examining the causes and consequences of unemployment among the educated youths in Kano, Nigeria. It also examined the reasons why some of them engaged in deviant behaviours. The role of government in eradicating this problem was also investigated. To ensure a comprehensive analysis of data, the study used a qualitative method. This involved in-depth interviews with 20 respondents whose responses were coded into themes according to the objectives of the study. The study revealed that unemployment among the respondents was triggered by a wide range of demographic, economic, social, psychological and cultural factors. Depending on the youths' psychological make-up and available resources, the findings show that unemployment had both detrimental and beneficial effects on the unemployed youths. In terms of negative outcomes, the results show that they suffered from poverty and experienced a wide range of health and psychological problems. Furthermore, some of them developed a negative outlook in life and became vulnerable to crime and deviation. However, unemployment also provided them an opportunity to be creative, resourceful and religious in order to cope with the crisis. In addition, the study also shows that despite the harsh effects of joblessness, very few were involved in deviant behaviours due to religiousity. The reasons for their involvement in crime and deviation are deprivation, frustration, feeling of rejection, lack of endurance and emotional trauma. Furthermore, the results also reveal that the government has a critical role to play in promoting the employability of educated youths. Therefore, the findings of the study call for a comprehensive and multi-dimensional approach to address the unemployment problem of this important segment of the Nigerian population.